Design Hidroponik Sederhana dari Botol Bekas sebagai Langkah Kreatif dan Ramah Lingkungan di SMA Kartika XIX-3 Cirebon: Assembling Simple Hydroponics from Wasted Bottles as Creative and Environmentally Friendly Steps in Senior High School - Gusman, Tania Avianda; Hirawati, Aulia Ghina; Khoirunniswati, Khoirunniswati; Jayanti, Dinda Dwi; Julaeha, Eha; Sahlan, Muhammad Yahdi; Zakiyyah, Zakiyyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Hydroponics is an innovation in cultivating plants even though the land is limited and does not require soil as a planting medium. Hydroponic plant nutrition is derived from vitamin solutions so that they dissolve in water. At the same time, the basic principle of hydroponics is to provide nutrients in a small space/land, and plants will grow more productively even without soil. The method of implementing this activity uses theoretical and practical learning methods. The hydroponic theory learning method is taught through lectures and discussions, while the experimental procedure is applied after receiving the material when making simple hydroponics. There are stages licensing and coordination stage, material delivery stage, and assistance in practice. The tools and materials for making simple hydroponics are scissors/cutters, shelves, used bottles, flannel cloth, sponge, plant seeds, and vitamins. This service program has obtained results and objectives as a means of developing students' creativity in managing used goods that are useful and have economic value. This program is also expected to foster students' entrepreneurial spirit in creating a hydroponic system at school using used bottles involving a series of creative and environmentally friendly steps. By collecting used bottles, designing systems with creativity, and educating students about hydroponics, this project creates an interactive learning environment and teaches the values of sustainability and the implementation of recycling. The division of tasks, use of recycled materials, and plant care involve students in every aspect of the project, promoting collaboration and a deep understanding of sustainability.